Improving Student Motivation in Mathematics Learning Thro - Eni Suheni; Indrie Noor Aini; Rika Mulyati Mustika, S.; Iyan Rosita Dewi Nur (Jurnal Locus Penelitian dan Pengabdian, 2026)
This study aims to analyze the effectiveness of gamification approaches integrated with Problem-Based Learning (PBL) in increasing students' learning motivation in mathematics learning. Low motivation to learn mathematics is a common problem in Indonesia, as evidenced by the results of PISA 2022 which shows that Indonesia's mathematics score only reaches 379 out of the OECD average score of 487. This study uses a quasi-experimental method with pretest-posttest control group design with the research subjects of 60 high school students in class X who are divided into experimental and control groups. The research instruments included a mathematics learning motivation questionnaire, a mathematical problem-solving ability test, an observation sheet, and an interview guideline. The results showed that the integration of gamification with PBL significantly increased students' learning motivation with an N-Gain of 0.68 (medium category), created a more interactive and enjoyable learning experience, and helped students understand mathematical concepts more deeply through contextual problem-solving. Gamification elements such as points, badges, levels, and leaderboards successfully create a competitive yet collaborative learning environment, while PBL encourages students to think critically and creatively in solving mathematical problems. Statistical tests showed significant differences (p < 0.05) between the experimental and control groups, indicating the effectiveness of this approach in increasing motivation to learn mathematics.